(untitled) - Tanner, L. E. (New York, 2006)
The great improvisational American jazz musicians of the mid-20th century inspired a generation of photographers to develop a looser, moodier style of visual expression. That evocative approach is on striking display in The Jazz Image. Covering six decades of performers from Louis Armstrong and Duke Ellington to John Coltrane and Miles Davisthis unique collection is as much a comprehensive catalogue of jazz greats as it is a salute to the photographers who captured them
Keywords: Photographic,Nhiếp ảnh,Nhạc sĩ Jazz,Jazz musicians